An Overview on Toxicity Reduction and Environmental Remediation - Harsha Vasudev Chaudhari; Javesh Kashinath Patil; Devshree Yashwantbhai Patel; Aniket Rajesing Girase; Hasni Hamid Yahiya Sayyed (Proceedings, 2024)
Toxicity reduction and environmental remediation are crucial aspects of addressing pollution and protecting ecosystems and human health [...]